2003
DOI: 10.1095/biolreprod.103.017293
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Imprinted Gene Methylation and Expression in Cloned Preimplantation Stage Mouse Embryos1

Abstract: Cloning by somatic cell nuclear transfer requires that epigenetic information possessed by the donor nucleus be reprogrammed to an embryonic state. Little is known, however, about this remodeling process, including when it occurs, its efficiency, and how well epigenetic markings characteristic of normal development are maintained. Examining the fate of epigenetic information associated with imprinted genes during clonal development offers one means of addressing these questions. We examined transcript abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
236
1
8

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(256 citation statements)
references
References 45 publications
11
236
1
8
Order By: Relevance
“…This is consistent with the widely reported abnormal gene expression in mouse and bovine NT embryos (Bortvin et al 2003;Daniels et al 2000;Han et al 2003;Mann et al 2003;Wrenzycki et al 2002;Wrenzycki et al 2001). Different from the cloned pig embryos, however, bovine and murine cloned embryos also have abnormal DNA methylation patterns (Kang et al 2001a), suggesting species differences in DNA methylation reprogramming.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with the widely reported abnormal gene expression in mouse and bovine NT embryos (Bortvin et al 2003;Daniels et al 2000;Han et al 2003;Mann et al 2003;Wrenzycki et al 2002;Wrenzycki et al 2001). Different from the cloned pig embryos, however, bovine and murine cloned embryos also have abnormal DNA methylation patterns (Kang et al 2001a), suggesting species differences in DNA methylation reprogramming.…”
Section: Discussionsupporting
confidence: 89%
“…However, little is known about this reprogramming process, and the overall success rate of animal cloning using somatic cells remains very low across different animal species, likely due to insufficient epigenetic reprogramming. Faulty or incomplete epigenetic reprogramming has been observed in different stages of development (Cezar et al 2003;Kang et al 2001b;Mann et al 2003). Even in cloned animals that survive to term, different aspects of epigenetic abnormalities are evident, although the majority of these animals appear to be healthy and normal (Archer et al 2003;Li et al 2004;Xue et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, when satellite sequences that had been examined in bovine (Kang et al, 2001a) were analyzed in a different species (porcine) methylation levels at the blastocyst stage of cloned embryos were more comparable to those of fertilized control embryos (Kang et al, 2001b), suggesting also species-specific differences. A recent study that analyzed several imprinted genes in cloned murine blastocysts showed that most of the examined genes displayed aberrant methylation and expression patterns (Mann et al, 2003).…”
Section: Dna Methylation and Ntmentioning
confidence: 99%
“…For somatic cell nuclear transfer to produce viable offspring requires that DNA remodeling and transcriptional reprogramming approximate that of the in vivo-produced embryo. The inefficiency of the epigenetic reprogramming is demonstrated by the analysis of transcription and methylation status of imprinted genes in the preimplantation stage mouse cloned embryo where only 4% of the SCNT derived embryos reproduced the expression of the imprinted genes H19, Meg3, Igf2r, Ascl2, and Snrpn relative to in vivo derived blastocysts (Mann et al, 2003). The cloned embryos were also found to have substantial loss of allele-specific DNA methylation at the imprinting control regions of the Snrpn and H19 genes.…”
Section: Introductionmentioning
confidence: 99%